2014
DOI: 10.1016/j.jorganchem.2014.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-induced emission behavior of a pincer platinum(II) complex bearing a poly(ethylene oxide) chain in aqueous solution

Abstract: An amphiphilic pincer platinum(II) complex with a poly(ethylene oxide) (PEO) chain exhibited aggregation-induced emission (AIE) because of micelle formation in water. The AIE activity was enhanced by the addition of 1,3,5-benzenetricarboxylic acid, which induced micelle formation through hydrogen-bonding interactions with the PEO chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Whilst we have tried our best to prepare a comprehensive review article, it is technically impossible for us to cover every piece of published papers, as the “old” papers are too numerous to enumerate and the “new” ones are published in a speed too fast to catch. In an effort to compensate this loss, we herein provide a list of representative papers published recently by different research laboratories in the world in the reference section. …”
Section: Discussionmentioning
confidence: 99%
“…Whilst we have tried our best to prepare a comprehensive review article, it is technically impossible for us to cover every piece of published papers, as the “old” papers are too numerous to enumerate and the “new” ones are published in a speed too fast to catch. In an effort to compensate this loss, we herein provide a list of representative papers published recently by different research laboratories in the world in the reference section. …”
Section: Discussionmentioning
confidence: 99%
“…In 2001, Tang et al discovered the very different light-emitting behaviors of some silole derivatives in solution and solid states. Weak or nonemissive in dilute solution but highly luminescent when their molecules aggregate in concentrated solutions or solid state, which has been defined as aggregation-induced emission (AIE). This discovery offers exciting inspirations to design and synthesize Pt II complexes with high EL performance, changing the emission behavior from ACQ to AIE. To date, some Pt II complexes with AIE character have been reported. , Huang’s group has established a series of ppy-type AIE-active Pt II complexes for bioimaging applications . Liu et al reported a series of Pt II diimine acetylide complexes with good AIE nature and optical power limiting property .…”
Section: Introductionmentioning
confidence: 99%